RETRACTED: Analysis of the efficiency of modern information technologies in e-learning and the use of interactive methods - Sigal Anatoliy; Bakumenko Maria; Titarenko Dmitriy (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001